Working Memory for Meaningless Manual Gestures. - Rudner, Mary (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2015)
Effects on working memory performance relating to item similarity have been linked to prior categori- sation of representations in long-term memory. However, there is evidence from gesture processing that this link may not be obligatory. The present study investigated whether working memory for incidentally generated meaningless manual gestures is influenced by formational similarity and whether this effect is modulated by working-memory load. Results showed that formational similarity did lower performance, demonstrating that similarity effects are not dependent on prior categorisation. However, this effect was only found when working-memory load was low, supporting a flexible resource allocation model according to which it is the quality rather than quantity of working memory representations that determines performance. This interpretation is in line with proposals suggesting language modality specific allocation of resources in working memory.